2022
DOI: 10.3389/fimmu.2022.1041098
|View full text |Cite
|
Sign up to set email alerts
|

Krebs von den lungen-6 as a clinical marker for hypersensitivity pneumonitis: A meta-analysis and bioinformatics analysis

Abstract: AimHypersensitivity pneumonitis (HP), also referred to as exogenous allergic alveolitis, is one of the most common interstitial lung diseases (ILDs). A potential immune biomarker, Krebs von den lgen-6 (KL-6) characterizes the progression and severity of HP. The meta-analysis in this study was conducted to elucidate the variations in the concentrations of KL-6 in different types of HP.MethodsA systematic search of various databases such as EMBASE, Pubmed, CNKI, VIP, Web of Science, and WanFang was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
3
0
2
Order By: Relevance
“…Moreover, the concentrations of serum KL-6 displayed a negative association with TLC and DLCO [66]. Based on a large meta-analysis [109], HP patients have a higher expression of KL-6 compared to normal individuals, with a substantial increase in patients with fibrotic HP. Elevated KL-6 concentrations were found to be closely linked to the progression of ILD as well as a substantial functional decline.…”
Section: Other Fibrosing Ildsmentioning
confidence: 99%
“…Moreover, the concentrations of serum KL-6 displayed a negative association with TLC and DLCO [66]. Based on a large meta-analysis [109], HP patients have a higher expression of KL-6 compared to normal individuals, with a substantial increase in patients with fibrotic HP. Elevated KL-6 concentrations were found to be closely linked to the progression of ILD as well as a substantial functional decline.…”
Section: Other Fibrosing Ildsmentioning
confidence: 99%
“…KL-6 levels have been reported to be increased in patients with HP compared to healthy individuals and could differentiate HP from IPF [ 133 ]. However, it remains unclear whether fibrotic or non-fibrotic HP exhibit higher levels of KL-6 [ 134 ]. In the study by Okamoto et al, KL-6 levels were not only higher in patients with chronic HP but also increased significantly during acute exacerbations of the disease [ 135 ].…”
Section: Biomarkers For Acute Exacerbations Of Hypersensitivity Pneum...mentioning
confidence: 99%
“…Krebs von den Lungen-6 (KL-6) is a high-molecular-weight glycoprotein encoded by the MUC1 gene, primarily located on the cell surface of type II alveolar epithelial cells and bronchial epithelial cells (10). Elevated serum levels of KL-6 have been identified as a biomarker for alveolar epithelial proliferation and injury in various respiratory conditions (10), including acute respiratory distress syndrome (11), hypersensitivity pneumonia (12), idiopathic interstitial pneumonia (13), pulmonary sarcoidosis (14), coronavirus disease 2019 (COVID-19) (15), and CTD-ILD (16). Furthermore, several studies have indicated the potential predictive value of serum KL-6 in determining the prognosis of individuals with severe lung conditions, including idiopathic pulmonary fibrosis (17) and COVID-19 (18).…”
Section: Introductionmentioning
confidence: 99%